Development of a contactless DC current sensor with high linearity and sensitivity based on the magnetoelectric effect. (8th May 2018) - Castro, N; Reis, S; Silva, M P; Correia, V; Lanceros-Mendez, S; Martins, P
Abstract: The magnetoelectric (ME) effect is increasingly being considered an attractive alternative for magnetic field and smart current sensing, being able to sense static and dynamic magnetic fields. This work reports on a contactless DC current sensor device based on a ME PVDF/Metglas composite, a solenoid and the corresponding electronic instrumentation. The ME sample shows a maximum resonant ME coefficient ( α 33 ) of 34.48 V cm −1 Oe −1, a linear response ( R 2 = 0.998) and a sensitivity of 6.7 mV A −1 . With the incorporation of a charge amplifier, an AC-RMS converter and a microcontroller the linearity is maintained ( R 2 = 0.997), the ME output voltage increases to a maximum of 2320 mV and the sensitivity rises to 476.5 mV A −1 . Such features allied to the highest sensitivity reported in the literature on polymer-based ME composites provide to the reported ME sensing device suitable characteristics to be used in non-contact electric current measurement, motor operational status checking, and condition monitoring of rechargeable batteries, among others.